The sustainability of pancasila values on improving the human resources of indonesian students in indonesian saudi arabian schools. Issue 1 (May 2021) - Masrukhin, A; Anwar, R; Sriyanto, H
Abstract: The focus of research on the application of the values of Pancasila on improving the human resources of Indonesian students in the Indonesian School of Saudi Arabia. Some of the objectives of this study are to analyze the cultural description of Indonesian student nationalism, reveal the behavioral tendencies and behavior of principals and teachers in enhancing nationalism. This study uses a phenomenological study of leadership culture in a qualitative descriptive form and the actions of principals and teachers.The urgent of this research complements research on practicing the value of Pancasila but with a different school context and culture.Therefore, expressing and analyzing the implementation of Pancasila values, researchers used leadership theory, cultural theory. Research results revealed that the implementation of Pancasila values of Indonesian students interacting with national standards of education and teaching Islamic values. The culture of environmental leadership and schools provides a positive response to the understanding of Indonesian student nationalism in Saudi Arabia, including pride and love for national identity.